Safety of total body irradiation using intensity-modulated radiation therapy by helical tomotherapy in allogeneic hematopoietic stem cell transplantation: a prospective pilot study. (5th September 2020) - Konishi, Tatsuya; Ogawa, Hiroaki; Najima, Yuho; Hashimoto, Shinpei; Wada, Atsushi; Adachi, Hiroto; Konuma, Ryosuke; Kishida, Yuya; Nagata, Akihito; Yamada, Yuta; Kaito, Satoshi; Mukae, Junichi; et al.
Abstract: Total body irradiation using intensity-modulated radiation therapy total body irradiation (IMRT-TBI) by helical tomotherapy in allogeneic hematopoietic stem cell transplantation (allo-HSCT) allows for precise evaluation and adjustment of radiation dosage. We conducted a single-center pilot study to evaluate the safety of IMRT-TBI for allo-HSCT recipients. Patients with hematological malignancies in remission who were scheduled for allo-HSCT with TBI-based myeloablative conditioning were eligible. The primary endpoint was the incidence of adverse events (AEs). Secondary endpoints were engraftment rate, overall survival, relapse rate, non-relapse mortality, and the incidence of acute and chronic graft-versus-host disease (aGVHD and cGVHD, respectively). Between July 2018 and November 2018, ten patients were recruited with a median observation duration of 571 days after allo-HSCT (range, 496–614). D80% for planning target volume (PTV) in all patients was 12.01 Gy. Average D80% values for lungs, kidneys and lenses (right/left) were 7.50, 9.03 and 4.41/4.03 Gy, respectively. Any early AEs (within 100 days of allo-HSCT) were reported in all patients. Eight patients experienced oral mucositis and gastrointestinal symptoms. One patient experienced Bearman criteria grade 3 regimen-related toxicity (kidney and liver). All cases achieved neutrophil engraftment. There was no grade III–IV aGVHD or late AE. One patient died of sinusoidal obstruction syndrome 67 days after allo-HSCT. The remaining nine patients were alive and disease-free at final follow-up. Thus, IMRT-TBI was well tolerated in terms of early AEs in adult patients who underwent allo-HSCT; this warrants further study with longer observation times to monitor late AEs and efficacy.